SISTEM INFORMASI MANAJEMEN PROYEK BERBASIS WEB PT MEDIA JAYA KONTRUKSI - Fajarrini, Novi; Coyanda, John Roni; Kesuma, Hendra Di (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The design of a Project Management Information System (PMIS) using the Program Evaluation and Review Technique (PERT) method at PT Media Jaya Konstruksi aims to optimize project scheduling planning and control. PERT was chosen because it can analyze uncertainties in project task completion time by estimating optimistic, pessimistic, and most likely durations. The system is designed to facilitate the company in managing the complexities of construction projects, estimating project duration, and identifying critical paths that impact project success. The system development methodology follows the PERT approach, encompassing the stages of requirements analysis, design, implementation, testing, and maintenance. Key features of the system include creating PERT diagrams, calculating critical paths, simulating project schedules, and generating automatic reports. Additionally, the system is equipped with an interactive dashboard to visualize project progress and support data-driven decision-making. The design results show that the PERT-based information system can help PT Media Jaya Konstruksi identify project bottlenecks earlier, reduce the risk of delays, and enhance project management efficiency. The system's implementation is expected to support the company in increasing competitiveness and maintaining client satisfaction through more structured and timely project completion.